Efficacy of the Dynesys Hybrid Surgery for Patients with Multi-Segmental Lumbar Spinal Stenosis - Xiao, Xiao; Chen, Gaoyang; Wang, Song; Liu, Junliang; Lin, Erhu; Chen, Ke; Xiang, Yucheng; Zhan, Ke; Liu, Congcong; Yuan, Zhengbin; Yang, Minjie; Zhong, Shuyuan; et al. (Frontiers in Surgery, 2022)
Objective: The efficacy of hybrid (Dynesys and fusion) surgery and the traditional fusion (TLIF) surgery were compared in patients with multi-segmental lumbar spinal stenosis. Methods: A total of 68 patients with multi-segmental lumbar spinal stenosis subjected to surgery were recruited between January 2013 and October 2020 in the First Affiliated Hospital of Southern University of Science and Technology (SUSTC). The patients were divided into the hybrid surgery group (N=33) and the TLIF group (N=35) by surgery. After surgery, follow-up was conducted for 12 months. Between the two groups, the following parameters were compared: general conditions, clinical symptom scores, imaging parameters, and early complications. Results: A statistically significant difference in the duration of surgery was noted between the two groups. After 12 months of follow-up, the ROM disappeared in the TLIF group, while 63.53% was preserved in the hybrid group with statistically significant differences. A statistically significant difference was identified in ODI at one week after surgery.Nonetheless, no statistically significant differences were observed at the 12-month post-surgical follow-up. Pfirrmann grade showed a 3.03% upper adjacent segment degeneration rate in the hybrid group (1/33) at 12-month follow-up and 2.86% (1/35) in the TLIF group. Notably, no early complications (screw loosening and wound infection) were identified in the two groups. Conclusion: The Dynesys hybrid surgery combined the advantages of two systems of dynamic stabilization and rigid fusion. Besides, hybrid surgery is potentially a novel approach for the treatment of multi-segment lumbar spinal stenosis.